Valorization of Food Processing By-Products - Chandrasekaran, Muthusamy;Ed (Fermented Foods and Beverages Series., 2013)
"This book addresses the issues, potentials, and prospects of harnessing various types of food processing byproducts through valorization and effective commercial utilization. After reviewing the state of food processing byproducts, the text introduces the basic principles of food and biotechnologies for valorization before providing a detailed description of byproducts and wastes generated. It identifies the